CENP-A nucleosome clusters form rosette-like structures around HJURP during G1 - Leonid Andronov (Nature Portfolio, 2019)
Human centromeric nucleosomes contain the specific CENP-A histone variant, which replaces canonical histone H3 and epigenetically marks the centromeres. Here the authors show that CENP-A nucleosomes form large supramolecular clusters during the G1 phase of the cell cycle which are arranged as rosette-like structures.